Message Admission Control along with Buffer Space Advertisement to Control Congestion in Delay Tolerant Networks (DTNs) - Farooq, Faiza; Bibi, Nargis (EAI Endorsed Transactions on Energy Web, 2018)
Delay and Disruption Tolerant networks (DTN) are subject to intermittent connection and long delay, thus the internet congestion control mechanisms are not suitable for DTNs. Data Delivery Rate and Delivery Delay are the parameters affected badly when network or part of a network is in congestion. In recent years, Congestion control strategies in DTNs are considered an active area for research. In this research a hybrid congestion control mechanism, Message Admission Control with Buffer Space Advertisement (MACBSA) is proposed which is based on MaxProp routing protocol. Preliminary results show the improvement in network performance while utilizing network resources efficiently.